PENGARUH PENERAPAN MODEL RADEC TERHADAP KEMAMPUAN MENULIS TEKS EKSPOSISI - Kristiani Tandi Rani; Usman Usman; Sakaria Sakaria (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The Effect of Applying the Radec Model on the Ability to Write Expositional Texts. This study is entitled "The Effect of Applying the RADEC Learning Model on the Ability to Write Exposition Texts in Grade VIII Students at SMP Negeri 27 Makassar. This study aims to describe the ability to write expository texts before, after, and the effect of applying the RADEC model to class VIII students of SMP Negeri 27 Makassar. This study is quantitative. The data in this study were obtained from students' pretest and posttest scores. Data analysis techniques used in this study used descriptive statistics using the SPSS version 21 test and inferential statistics by carrying out normality tests, homogeneity tests, and effectiveness tests. The results of the data homogeneity test showed a sig value of 0.639 > 0.05, so the data was called homogeneous. The results of the one sample test showed that the t count > t table, namely 3,282 > 2,009, supported the hypothesis H0, namely that the use of the RADEC learning model was effectively used in learning to write exposition texts for class VIII students of SMP Negeri 27 Makassar.